AGREE II for TCM: Tailored to evaluate methodological quality of TCM clinical practice guidelines - Xie, Xiuli; Wang, Yangyang; Li, Hui (Frontiers in Pharmacology, 2023)
AGREE II has been widely used in the methodological quality assessment of clinical practice guidelines. Chinese medicine clinical practice guidelines have unique characteristics which distinguish them from those of Western medicine, such as syndrome differentiation and treatment. As such, some domains and items in AGREE II are unsuitable for assessing TCM clinical practice guidelines. Therefore, adjustment and expansion of AGREE II are needed for it to be applicable to TCM. Purpose: Adjust and expand AGREE II to be suitable for evaluating the methodological quality of TCM clinical practice guidelines. Methods: First, we established a research working group. Second, we performed a systematic literature search and screening of TCM guidelines. Two researchers used AGREE Ⅱ to evaluate the quality of the included guidelines. Based on the evaluation experience, the two reviewers suggested adjustments and supplementary comments applicable to TCM guidelines for some items of AGREE Ⅱ, and drafted an initial version of AGREE Ⅱ for TCM. Third, we integrated the suggestions in the literature for the development and evaluation of TCM clinical guidelines, and improved the initial version. Fourth, we invited 16 experts to conduct an expert consensus on the initial version. Results: Based on the evaluation of the TCM guideline experience, the two evaluators offered adjustments and supplementary comments for AGREE Ⅱ Items 1, 7, 10, 11, 12, 15, and 18, and drafted the initial version of AGREE Ⅱ for TCM. Combined with the suggestions from the literature on TCM clinical guideline development and quality evaluation, the core working group proposed modifying AGREE Ⅱ Instrument Items 2, 4, 5, 8, 9, 13, 20 and 21, to improve the initial version of AGREE Ⅱ for TCM. We conducted an expert consensus on this improved initial version of AGREE. The results of the first round of expert surveys showed that experts are in strong agreement regarding the initial version of AGREE Ⅱ for TCM. Conclusion: Based on the characteristics of the TCM clinical practice guidelines, we adjusted and expanded AGREE II to create AGREE II for TCM. This version is suitable for the methodological quality assessment of TCM clinical practice guidelines.